1-(2′,4′-Difluorobiphenyl-4-yl)ethanone - Guo, Meng-Ping (International Union of Crystallography, 2008)
In the crystal structure of the title compound, C(14)H(10)F(2)O, the dihedral angles between the benzene rings in the two crystallographically independent molecules are 46.9 (2) and 47.6 (2)°. The molecules are linked into dimers by C—H⋯F interactions and these dimers are further stacked into columns along the b axis by π–π interactions between the benzene rings [centroid–centroid distance = 3.8221 Å; the dihedral angle between the planes of these rings is 4.87 (2)°]. In addition, C—F⋯π interactions also contribute to the crystal packing (C⋯centroid distance = 3.5919 Å).